Implementation of structured feedback in a psychiatry residency program in Canada: a qualitative analysis study - Thakur, Anupam; Darani, Shaheen; Kalocsai, Csilla; Silver, Ivan; Sockalingam, Sanjeev; Soklaridis, Sophie (Frontiers in Psychiatry, 2023)
Introduction Structured feedback is important to support learner progression in competency-based medical education (CBME). R2C2 is an evidence-based four-phased feedback model that has been studied in a range of learner contexts; however, data on factors influencing implementation of this model are lacking. This pilot study describes implementation of the R2C2 model in a psychiatry CBME residency program, using the Consolidated Framework for Implementation Research (CFIR). Methods The study was carried out in three phases: planning, implementation and evaluation. After receiving training, 15 supervisors used the R2C2 feedback model with residents. Semi-structured interviews explored (n = 10) supervisors’ experience of the model. CFIR was used to identify factors that influence implementation of the R2C2 model when providing feedback to residents. Results Qualitative data analysis revealed four key themes: Perceptions about the R2C2 model, Facilitators and barriers to its implementation, Fidelity to R2C2 model and Intersectionality related to the feedback. The CFIR implementation domains provided structure to the themes and subthemes. Conclusion The R2C2 model is a helpful tool to provide structured feedback. Structure of the model, self-efficacy, in-house educational expertise, learning culture, organizational readiness, and training support are important facilitators of implementation. Further studies are needed to explore the learner’s perspective and fidelity of this model.